2010
DOI: 10.1017/s0033291710000607
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and specificity of computer-assisted cognitive remediation in schizophrenia: a meta-analytical study

Abstract: The results lend support to the efficacy of CACR with particular emphasis on Social Cognition. The difficulty in targeting specific domains suggests a 'non-specific' effect of CACR. These results are discussed in the light of the possible bias in remediation tasks due to computer interface design paradigms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
147
4
16

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(176 citation statements)
references
References 46 publications
9
147
4
16
Order By: Relevance
“…In the Wykes et al (38) meta-analysis, underpowered sample sizes (60%), lack of independent randomization (70%), lack of treatment fidelity assessment (80%), and lack of allocation masking (73%) were frequently observed. In the Grynszpan et al (40) meta-analysis, 63% of the studies use a treatment-as-usual (TUA) control arm, which fails to control for the non-specific effects of the activities involved in participating in a cognitive remediation study. Revell et al (39) found a much larger effect of cognitive remediation in open label trials (0.54) compared to blinded ones (0.08).…”
Section: Cognitive Remediationmentioning
confidence: 99%
“…In the Wykes et al (38) meta-analysis, underpowered sample sizes (60%), lack of independent randomization (70%), lack of treatment fidelity assessment (80%), and lack of allocation masking (73%) were frequently observed. In the Grynszpan et al (40) meta-analysis, 63% of the studies use a treatment-as-usual (TUA) control arm, which fails to control for the non-specific effects of the activities involved in participating in a cognitive remediation study. Revell et al (39) found a much larger effect of cognitive remediation in open label trials (0.54) compared to blinded ones (0.08).…”
Section: Cognitive Remediationmentioning
confidence: 99%
“…CACR comprende un grupo de técnicas de entrenamiento a partir de software, capaces de tratar de manera selectiva diferentes dominios cognitivos 39 . Numerosos estudios han demostrado que CACR puede tener efectos sobre la sintomatología psicótica y el funcionamiento psicosocial, en pacientes con esquizofrenia 40 .…”
Section: Computer-assisted Cognitive Remediation (Cacr) Techniquesunclassified
“…Essa busca tinha por finalidade encontrar estudos sobre intervenções psicoterápicas utilizando conceitos sociocognitivos e resultou em 11 artigos 2,6-15 , dos quais um foi excluído por não se tratar de um ensaio clínico 7 . Outros 10 manuscritos 3,[16][17][18][19][20][21][22][23][24] foram selecionados a partir da leitura dos artigos acima, pois pareciam preencher os critérios de inclusão do tema a ser discutido.…”
Section: Métodosunclassified